[PP.14.27] COMPARATIVE ANALYSIS OF MIRNA EXPRESSION IN SERUM AND PLASMA OF PATIENTS WITH ACUTE MYOCARDIAL INFARCTION. (September 2017) - Hermenegildo, C.; Mompeon, A.; Januario, T.; Vidal-Gomez, X.; Pujol, M.; Perez-Cremades, D.; García-Blas, S.; Ortega, L.; Sanchis, J.; Dantas, A.P.; Novella, S.
Abstract : Objective: miRNAs are present in human biofluids and have been pointed as potential biomarkers for diagnosis and assessment of prognosis of different cardiovascular diseases. Nevertheless, previous reports have suggested that different methodological variances could affect miRNA concentration. In this study we aim to compare the expression of major miRNAs associated with acute myocardial infarction (AMI) in plasma and serum from Non-ST-elevation myocardial infarction (NSTEMI) patients relative to samples from healthy volunteers. Design and method: Plasma and corresponding serum samples were collected from healthy individuals (n = 20) and NSTEMI patients (n = 40) prior to coronary angioplasty. Blood was collected into anti-coagulant free (for serum) and EDTA Vacutainer® (for plasma) tubes. Circulating miRNA was purificated using miRCURY RNA Isolation Kit (Exiqon). 50 ng of RNA was used for reverse transcription of the selected miRNAs (miRNA-21, miRNA-26a, miRNA-92a, and miRNA-133a). TaqMan MicroRNA Assays were used to assess the expression of individual miRNAs. Relative quantification was performed using QuantStudio Software. Values were normalized to the expression of the reference gene RNU6 and miRNA-484. Results: miRNA yield was similar in samples from plasma and serum. The expression level of RNU6 and miR-484 was similar in samples from plasma and serum. Nevertheless, we observed a higher variability of RNU6 in plasma than in serum, and we chose miRNA-484 as endogenous control. miRNA-26a decreased in samples from AMI patients showing the same pattern expression in serum and plasma (36 ± 5% and 18 ± 6% of control values, respectively, p < 0.01). miRNA-133a increased in serum (482 ± 78%, p < 0.01) and showed a slight increase in plasma (157% of control values, p > 0.05) from AMI patients. miRNA-92a expression was decreased only in plasma samples (33 ± 4%, p < 0.01), and miR-21 showed an opposite pattern expression, being 10-fold increased in serum (p < 0.05) and decreased in plasma (32 ± 9%, p < 0.05). Conclusions: Plasma and serum exhibit different pattern of circulating miRNA expression in patients with AMI and suggest that results from studies with different starting material could not be comparable. These results call our attention to the importance of maintaining methodological care in when determining the expression of miRNA in patients.